SIRT1 attenuates high glucose-induced insulin resistance via reducing mitochondrial dysfunction in skeletal muscle cells. (May 2015) - Zhang, Hao-Hao; Ma, Xiao-Jun; Wu, Li-Na; Zhao, Yan-Yan; Zhang, Peng-Yu; Zhang, Ying-Hui; Shao, Ming-Wei; Liu, Fei; Li, Fei; Qin, Gui-Jun
Insulin resistance is often characterized as the most critical factor contributing to the development of type 2 diabetes mellitus (T2DM). Sustained high glucose is an important extracellular environment that induces insulin resistance. Acquired insulin resistance is associated with reduced insulin-stimulated mitochondrial activity as a result of increased mitochondrial dysfunction. Silent information regulator 1 (SIRT1) is one member of the SIRT2 (Sir2)-like family of proteins involved in glucose homeostasis and insulin secretion in mammals. Although SIRT1 has a therapeutic effect on metabolic deterioration in insulin resistance, it is still not clear how SIRT1 is involved in the development of insulin resistance. Here, we demonstrate that pcDNA3.1 vector-mediated overexpression of SIRT1 attenuates insulin resistance in the high glucose-induced insulin-resistant skeleton muscle cells. These beneficial effects were associated with ameliorated mitochondrial dysfunction. Further studies have demonstrated that SIRT1 restores mitochondrial complex I activity leading to decreased oxidative stress and mitochondrial dysfunction. Furthermore, SIRT1 significantly elevated the level of another SIRT which is named SIRT3, and SIRT3 siRNA-suppressed SIRT1-induced mitochondria complex activity increments. Taken together, these results showed that SIRT1 improves insulin sensitivity via the amelioration of mitochondrial dysfunction, and this is achieved through the SIRT1–SIRT3–mitochondrial complex I pathway.